Structural-functional aspects of central nervous system pathology - Nasibullin, B. A.; Gozhenko, A. I.; Volkov, M. A.; Zukow, W. (Journal of Education, Health and Sport, 2026)
How tissues remain functional while injured is one of the oldest questions in pathology, and one for which Virchow’s axiom — that disease introduces nothing new, only displaces what is already there — still frames the modern debate1,2. The conventional clinical-pathological framework treats the diseased cell as a single object that either survives or dies3,4, but tissues are mosaics of cellular subpopulations whose collective behaviour determines whether an organ adapts or fails. Here we show, in a 21-day rat model of unilateral cerebrovascular insufficiency induced by left common carotid artery ligation, that chronic ischaemia drives a coordinated, time-resolved reorganisation of neuronal subpopulations in three cortical and thalamic regions of differing vascular accessibility. The fraction of normochromic neurons declines progressively, while neurons with structural signatures of heightened functional activity and, later, of intensified regeneration expand to take their place. In parallel, neuronal subpopulations using the tricarboxylic-acid cycle in a balanced manner give way to subpopulations relying on unbalanced ‘emergency’ variants, but only in deeper structures with limited collateral supply. These results indicate that tissue adaptation to a sustained insult is a structured, region-specific redistribution of pre-existing cellular phenotypes — a typological response that supports Virchow’s view and provides a quantitative template for cellular pathology research more broadly.